2021
DOI: 10.1016/j.jretconser.2021.102516
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in consumer behavior towards organic products: Theory-driven data analytics

Abstract: Consumer behavior is key in shifts towards organic products. A diversity of factors influences consumer preferences, driving planned, impulsive, and unplanned purchasing decisions. We study choices among organic and conventional wine using an extensive survey among Australian consumers (N=1003). We integrate five behavioral theories in the survey design, and use supervised and unsupervised machine learning algorithms for analysis. We quantify a gap between intention and behavior, and emphasize the importance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 49 publications
0
35
0
2
Order By: Relevance
“…Compared to them, 36-40% of those who had a decent living appreciated the importance of organic vegetables and fruit. Such an attitude is conditioned by the media misrepresenting organic products as overpriced [65]. Sánchez-Bravo et al reported the same results regard-ing consumers' intention to pay a higher price for eco-friendly products [66].…”
Section: Discussionmentioning
confidence: 91%
“…Compared to them, 36-40% of those who had a decent living appreciated the importance of organic vegetables and fruit. Such an attitude is conditioned by the media misrepresenting organic products as overpriced [65]. Sánchez-Bravo et al reported the same results regard-ing consumers' intention to pay a higher price for eco-friendly products [66].…”
Section: Discussionmentioning
confidence: 91%
“…The research results showed that these commercial recognition systems have different processing results when processing distorted images and some suggestions are provided for developers in response to the existing problems ( Yang et al, 2021 ). Taghikhah et al (2021) studied the influence of consumer behavior on product purchase decisions. Supervised and unsupervised machine learning algorithms were used and behavioral theory was combined to quantify the intentions and behaviors of consumers, so as to realize the combination of emotional factors and normative cues to predict the buying behavior of consumers ( Taghikhah et al, 2021 ).…”
Section: Related Workmentioning
confidence: 99%
“… Taghikhah et al (2021) studied the influence of consumer behavior on product purchase decisions. Supervised and unsupervised machine learning algorithms were used and behavioral theory was combined to quantify the intentions and behaviors of consumers, so as to realize the combination of emotional factors and normative cues to predict the buying behavior of consumers ( Taghikhah et al, 2021 ). Lixăndroiu et al (2021) studied the influence of personality characteristics and attitudes toward the Internet on traditional electronic online shopping and augmented reality E-commerce.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, based on the most recent contributions from scholars more dedicated to the benefits of technology for overall business sustainability [33,57], we can expect future advancements on demonstrating transversal organisational gains, such as cost reduction and augmented decision-making capabilities provided by big data analytics. The potential benefits arising from co-creation opportunities, AI and machine learning are suggested [60,61], which may disrupt the competitive landscape for food industry and hospitality, per example, by enabling players with proactive flexibility for more robust marketing applications and supply chain competitive advantages, because of demand forecasts driven by big data and more interactive relationships with customers.…”
Section: Review Of Theories Framework and Literature On The Role Of New Technologies And Accelerating The Innovation Roadmapmentioning
confidence: 99%